Iterated Oscillation Criteria for Delay Dynamic Equations of First Order - B. Karpuz (Advances in Difference Equations, 2009)
We obtain new sufficient conditions for the oscillation of all solutions of first-order delay dynamic equations on arbitrary time scales, hence combining and extending results for corresponding differential and difference equations. Examples, some of which coincide with well-known results on particular time scales, are provided to illustrate the applicability of our results.